Association of Implementation of Practice Standards for Electrocardiographic Monitoring With Nurses' Knowledge, Quality of Care, and Patient Outcomes: Findings From the Practical Use of the Latest Standards of Electrocardiography (PULSE) Trial. (February 2017) - Funk, Marjorie; Fennie, Kristopher P.; Stephens, Kimberly E.; May, Jeanine L.; Winkler, Catherine G.; Drew, Barbara J.; Borman, Barbara; Calcasola, Stephanie; Carey, Mary; Currie, Laura; Davis, Leslie; Fitzpatrick, Eleanor; et al.
Abstract : Background—: Although continuous electrocardiographic (ECG) monitoring is ubiquitous in hospitals, monitoring practices are inconsistent. We evaluated implementation of American Heart Association practice standards for ECG monitoring on nurses' knowledge, quality of care, and patient outcomes. Methods and Results—: The PULSE (Practical Use of the Latest Standards of Electrocardiography) Trial was a 6-year multisite randomized clinical trial with crossover that took place in 65 cardiac units in 17 hospitals. We measured outcomes at baseline, time 2 after group 1 hospitals received the intervention, and time 3 after group 2 hospitals received the intervention. Measurement periods were 15 months apart. The 2-part intervention consisted of an online ECG monitoring education program and strategies to implement and sustain change in practice. Nurses' knowledge (N=3013 nurses) was measured by a validated 20-item online test, quality of care related to ECG monitoring (N=4587 patients) by on-site observation, and patient outcomes (mortality, in-hospital myocardial infarction, and not surviving a cardiac arrest; N=95 884 hospital admissions) by review of administrative, laboratory, and medical record data. Nurses' knowledge improved significantly immediately after the intervention in both groups but was not sustained 15 months later. For most measures of quality of care (accurate electrode placement, accurate rhythm interpretation, appropriate monitoring, and ST-segment monitoring when indicated), the intervention was associated with significant improvement, which was sustained 15 months later. Of the 3 patient outcomes, only in-hospital myocardial infarction declined significantly after the intervention and was sustained. Conclusions—: Online ECG monitoring education and strategies to change practice can lead to improved nurses' knowledge, quality of care, and patient outcomes. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01269736. Abstract : Supplemental Digital Content is available in the text.